Paving method with enhancing adhesivity and durability by using emulsified asphalt composition
Patent Information
- Application Number
- KR1020250029668
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2026-09-17
Smart Images

Figure PAT00012_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to an asphalt road paving method that significantly improves the stability and lifespan of road pavement by using an asphalt concrete primer of a specific composition and an emulsified asphalt of a specific composition when constructing a new asphalt road, repairing a damaged asphalt road, or overlaying asphalt. Background Technology
[0003] The use of asphalt to waterproof the gaps in fortress walls dates back to ancient Egypt and other places 5,000 years ago, and since then, asphalt has been widely used for road paving.
[0004] The above asphalt is divided into types such as natural asphalt, petroleum-based asphalt, and paving tar, and straight asphalt and emulsified asphalt are widely known.
[0005] In addition, the above asphalt is used as a binder or adhesive material because it has excellent adhesive properties and excellent adhesion to mineral materials. It is also used as a waterproofing material because it is insoluble in water and impermeable. Furthermore, since its viscosity can be varied according to the purpose of use, it has a diverse range of applications and is used for various purposes such as road paving, waterproofing, general industrial use, and agricultural use.
[0006] Asphalt used for road paving is petroleum-based asphalt, and straight asphalt with excellent adhesion, ductility, and water absorption is generally used.
[0007] Korean Registered Patent No. 2385509 discloses an emulsified asphalt comprising asphalt, a viscosity reducing agent, an anti-stripping agent, etc., and discloses a construction method in which 5 to 8 mm aggregate is spread on top of the emulsified asphalt before it hardens after the emulsified asphalt is sprayed to bond the asphalt and the aggregate. In this paving method, which involves spraying emulsified asphalt onto an existing pavement surface and then spreading aggregate on top of it, the emulsified asphalt has the advantage of being easy to handle as it is in a liquid state without heating at room temperature. However, since the composition contains more than 50% by weight of water based on 100% by weight of the total weight, it has the disadvantage of requiring a long curing time for the water to evaporate after construction, and it has the disadvantage of having weaker adhesion than straight asphalt or modified asphalt due to the characteristics of the emulsified asphalt.
[0008] In particular, conventional emulsified asphalt methods suffered from low viscosity, which prevented stable fixation on slopes or in high-load areas, and weak interlayer bonding, leading to easy detachment after construction. There were also limitations, such as reduced resistance to road surface wear and damage due to a low sieve residue ratio, and increased long-term maintenance costs. Furthermore, the low penetration of evaporated residues caused sensitivity to temperature changes and vehicle loads, leading to easy cracking. Additionally, there were issues with environmental pollution caused by dust dispersion during work, and work efficiency problems resulting in prolonged construction times due to repetitive tasks as only thin layers could be applied. Prior art literature
[0010] Korean Registered Patent No. 10-2385509 (Publication Date: April 1, 2024) Korean Registered Patent No. 10-2438241 (Publication Date: August 31, 2022) The problem to be solved
[0011] Accordingly, the inventors intend to provide a paving method using emulsified asphalt that can improve the low durability of existing emulsified asphalt, the inconvenience of construction on slopes or high-load areas, and the low durability of the constructed road when paving roads with emulsified asphalt. means of solving the problem
[0013] The paving method of the present invention for achieving the above-mentioned purpose performs a process comprising: a first step of preparing an asphalt road surface; a second step of forming a primer layer by applying an asphalt primer to the surface prepared in the first step; a third step of laying emulsified asphalt on the primer layer; a fourth step of compacting the laid area; and a fifth step of finishing.
[0014] At this time, the asphalt primer comprises straight asphalt, urethane-modified silicone polymer resin, epoxy-modified acrylic copolymer resin, penetration enhancer, flow enhancer, and solvent.
[0015] In addition, the emulsified asphalt comprises straight asphalt, petroleum resin, urethane-modified silicone polymer resin, acrylic binder resin, flux oil, petroleum resin, surfactant, aggregate, filler, thickener, plasticizer, vegetable emulsifier, dispersant, and water. Effects of the invention
[0017] The asphalt primer used in the paving method of the present invention has high viscosity, which prevents scattering during work and allows the emulsified asphalt to be stably fixed even on slopes, and can significantly improve the bonding strength of the asphalt layer to the ground. In addition, the emulsified asphalt used in the paving method of the present invention has a high sieve residue ratio, which forms a harder asphalt layer on the road surface, fills microcracks, significantly improves durability against wear and damage, and provides excellent crack prevention effects. Brief explanation of the drawing
[0019] Figure 1 is a photograph of an actual construction project in which road paving was performed using the paving method of the present invention. Specific details for implementing the invention
[0020] The present invention will be described in more detail below.
[0021] As a preferred embodiment, the asphalt road paving method of the present invention performs a process comprising: a first step of preparing the asphalt road surface as shown in the photograph in FIG. 1; a second step of forming a primer layer by applying an asphalt primer to the surface prepared in the first step; a third step of laying emulsified asphalt on the primer layer; a fourth step of compacting the laid area; and a fifth step of finishing treatment.
[0022] In addition, the paving method of the present invention may further perform any one of the following processes as needed: a process of forming a surface coating layer by coating with a peelcoat agent between step 1 and step 5; and a process of forming a surface coating layer with an asphalt tack coating spray.
[0023] The above surface preparation in Step 1 means removing foreign substances and removing all or part of the existing asphalt pavement in the area where the paving method of the present invention is applied. For example, the existing asphalt in the road paving construction area is cut using a crusher, and the crushed material and the surface are prepared.
[0025] Step 2 is a process of forming a primer layer by applying an asphalt primer to the surface of the prepared surface to increase the bonding strength between the prepared surface and the emulsified asphalt layer formed by laying, and to facilitate the laying of Step 3 even on slopes.
[0027] Asphalt primer
[0028] The asphalt primer of the second stage comprises straight asphalt, urethane-modified silicone polymer resin, epoxy-modified acrylic copolymer resin, a penetration enhancer, a fluidity enhancer, and a solvent, preferably comprising 10 to 15 weight% of straight asphalt, 25 to 45 weight% of urethane-modified silicone polymer resin, 20 to 30 weight% of epoxy-modified acrylic copolymer resin, 5 to 8 weight% of penetration enhancer, 2 to 5 weight% of fluidity enhancer, and the remaining amount of solvent among 100 weight%, more preferably comprising 12 to 15 weight% of straight asphalt, 30 to 40 weight% of urethane-modified silicone polymer resin, 22 to 28 weight% of epoxy-modified acrylic copolymer resin, 6 to 8 weight% of penetration enhancer, 2 to 4 weight% of fluidity enhancer, and the remaining amount of solvent among 100 weight%.
[0029] The above urethane-modified silicone polymer resin and epoxy-modified acrylic copolymer resin are used together to serve as a primer that significantly improves the adhesion of the emulsified asphalt layer, and the above urethane-modified silicone polymer resin includes a compound represented by the following chemical formula 1. Furthermore, if the content thereof is less than 25% by weight of the total weight of the primer, the amount used is insufficient and the effect of improving adhesion may be negligible, and if it is used in excess of 45% by weight, the viscosity of the primer is too high, which may result in poor workability during construction.
[0030] [Chemical Formula 1]
[0031]
[0032] In Chemical Formula 1, R 1 is -CH2OCH2CH3, -CH2OCH(CH3)2, or -CH2O(CH3)3, preferably -CH2OCH(CH3)2 or -CH2O(CH3)3. And, the above R of Chemical Formula 1 2is a C2-C3 straight-chain alkylene group, preferably a propylene group. In addition, the above R of Formula 1 3 Is is, R 4 is a hydrogen atom, a C1-C3 straight-chain alkyl group, or -CH2OCH3, preferably R 4 is a C1 to C3 straight-chain alkyl group. Also, m in Chemical Formula 1 is an integer from 1 to 3, preferably 2 or 3. In addition, , * denotes a bonding site.
[0033] If the content of the epoxy-modified acrylic copolymer resin in the asphalt primer composition is less than 20 weight%, the effect of improving adhesion may be insufficient, and if used in excess of 30 weight%, there may be a problem of reduced miscibility between the compositions within the primer.
[0034] And, the epoxy-modified acrylic copolymer resin is a copolymer produced by copolymerizing a reaction solution comprising a mixed monomer, an acrylate represented by the following chemical formula 2, a polymerization initiator, and a solvent. Preferably, the reaction solution comprises 50 to 55 weight% of the mixed monomer, 2.0 to 3.5 weight% of the acrylate, 0.2 to 1.5 weight% of the polymerization initiator, and the remainder of 100 weight% of the solvent. More preferably, the reaction solution may comprise 51.5 to 53.5 weight% of the mixed monomer, 2.5 to 3.5 weight% of the acrylate, 0.4 to 1.2 weight% of the polymerization initiator, and the remainder of 100 weight% of the solvent.
[0035] [Chemical Formula 2]
[0036]
[0037] In Chemical Formula 2, R 1 is a C2 to C5 straight-chain alkylene group, preferably an ethylene group or an n-propylene group. In addition, R of Formula 2 2 It is a hydrogen atom or -OR 3 is. And, the above R3 is a C1-C8 straight-chain alkyl group or a phenyl group, preferably a C1-C8 straight-chain alkyl group.
[0038] In addition, the mixed monomer used in the synthesis of the epoxy-modified acrylic copolymer resin comprises glycidyl methacrylate and n-propyl methacrylate, and preferably may comprise 40 to 50 weight% of glycidyl methacrylate and 50 to 60 weight% of n-propyl methacrylate.
[0039] And, the polymerization initiator used in the synthesis of the epoxy-modified acrylic copolymer resin may comprise one or more selected from TAPO (tert-amylperoxy 2-hexanoate), 4-phenoxydichloroacetphenone, 4-t-butyldichloroacetphenone, 4-t-butyltrichloroacetphenone, diethoxyacetphenone, 2-hydroxy-2-methyl-l-phenylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-l-one, and 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropan-1-one, and preferably TAPO, 2-hydroxy-2-methyl-l-phenylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-l-one and It may include one or more selected from 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropan-1-one, and more preferably, it may include one or more selected from TAPO, 2-hydroxy-2-methyl-l-phenylpropan-1-one and 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-l-one.
[0040] The solvent used in the synthesis of the epoxy-modified acrylic copolymer resin may include one or more selected from methyl acetate, ethyl acetate, butyl acetate, and propylene glycol methoxy acetate.
[0041] In addition, the penetration enhancer in the asphalt primer composition plays a role in ensuring that the primer is well absorbed and dispersed on a surface prepared, and may include one or more selected from potassium (C1-C5 alkyl) siliconate and 3-iodo-2-propynyl-N-butyl carbamate, and preferably may include potassium (C2-C3 alkyl) siliconate and 3-iodo-2-propynyl-N-butyl carbamate in a weight ratio of 1:0.30 to 0.40. Furthermore, if the content of the penetration enhancer in the total weight% of the asphalt primer is less than 5 weight%, the penetration effect of the primer on the surface prepared may be insufficient, and using more than 8.0 weight% is uneconomical and may rather reduce the adhesion enhancement effect of the primer, so it is appropriate to use it within the above range.
[0042] In addition, the above-mentioned fluidity enhancer in the asphalt primer composition plays a role in increasing the miscibility between primer compositions and increasing the spreadability of the primer, and it is preferable to use one comprising 12 to 16 weight% of polyoxyethylene lauryl ether and 84 to 88 weight% of hydrocarbon oil with an aromatic compound content of less than 0.5 weight%. Furthermore, if the content of the fluidity enhancer in the total weight% of the asphalt primer is less than 2 weight%, the effect of increasing the fluidity of the primer due to its use is insufficient, and if it is used in excess of 5 weight%, there may be a problem where the viscosity of the primer decreases rapidly; therefore, it is appropriate to use it within the above range.
[0043] In addition, the solvent in the asphalt primer composition includes one or more selected from n-hexane, ethyl cellosolve, and furfuryl alcohol. Preferably, using a mixture of three types of n-hexane, ethyl cellosolve, and furfuryl alcohol is advantageous in terms of miscibility and solubility between materials. More preferably, it is better to use a mixture of n-hexane, ethyl cellosolve, and furfuryl alcohol in a volume ratio of 1:0.20 to 0.40:0.10 to 0.30.
[0044] Also, the application of the second stage asphalt primer uses a general application method used in the industry and is not specifically limited.
[0045] The asphalt primer prepared with the above composition in the above content satisfies the KS M 2203:2021 standard viscosity (Engler degree, 25℃) of 4.
[0047] Next, the third step of the paving method of the present invention is a process of laying emulsified asphalt on the surface where the asphalt primer was applied in the second step.
[0048] emulsified asphalt
[0049] The above emulsified asphalt can be any emulsified asphalt for coating paving commonly used in the industry, and preferably, it is advantageous to use an emulsified asphalt with the following composition in terms of compatibility with the two-stage asphalt primer and the effect of increasing bonding strength.
[0050] The above emulsified asphalt comprises an asphalt composition including straight asphalt, urethane-modified silicone polymer resin, acrylic binder resin, flux oil, petroleum resin, surfactant, thickener, plasticizer, vegetable emulsifier, dispersant, and water; recycled aggregate including aggregate and filler; and water, preferably the asphalt composition and recycled aggregate may be included in a weight ratio of 1:8 to 10, more preferably in a weight ratio of 1:8.5 to 9.5.
[0051] In addition, water is mixed in an appropriate amount according to the construction environment before laying the emulsified asphalt to ensure the emulsified asphalt has the correct mixability and viscosity.
[0053] Among the emulsified asphalt compositions, the asphalt composition may comprise 50 to 58 wt% straight asphalt, 1.0 to 2.5 wt% urethane-modified silicone polymer resin, 2.0 to 8.5 wt% acrylic binder resin, 0.2 to 1.0 wt% flux oil, 0.3 to 1.0 wt% petroleum resin, 0.05 to 0.20 wt% surfactant, 0.5 to 1.5 wt% thickener, 0.2 to 1.0 wt% plasticizer, 0.1 to 1.0 wt% vegetable emulsifier, 1.0 to 3.0 wt% dispersant, and the remaining amount of water out of 100 wt%, and preferably 50 to 55 wt% straight asphalt, 1.0 to 1.8 wt% urethane-modified silicone polymer resin, 4.0 to 8.0 wt% acrylic binder resin, 0.3 to It may contain 0.8 wt% petroleum resin, 0.4 to 1.0 wt% surfactant, 0.05 to 0.15 wt% thickener, 0.5 to 1.5 wt% plasticizer, 0.2 to 0.5 wt% vegetable emulsifier, 1.5 to 2.5 wt% dispersant, and the remaining amount of water out of 100 wt%.
[0055] Among the above asphalt compositions, the straight asphalt serves as the main component of emulsified asphalt and plays a role in providing adhesion between recycled aggregates; the straight asphalt is extracted from crude oil without altering the asphalt components as much as possible. Generally, asphalt is a form in which a solid polymer called asphaltene is dispersed within a highly viscous oily or resinous substance called petroleum or marten. The straight asphalt is primarily governed by the properties of petroleum, exhibiting excellent elasticity and adhesion, and thus can display properties suitable for road paving materials. As a preferred example, AP-3 and / or AP-5 may be used for the straight asphalt, but is not limited thereto. Furthermore, if this content is less than 50 weight percent in the asphalt composition, the mechanical properties of the laid and cured asphalt layer may be poor, and if it exceeds 58 weight percent, it is uneconomical.
[0056] Next, the urethane-modified silicone polymer resin among the asphalt composition components is the same as the urethane-modified silicone polymer resin described in the second stage asphalt primer. By applying it to the emulsified asphalt, the bonding strength with the asphalt primer can be significantly improved. Furthermore, if the content of it in the asphalt composition is less than 1.0 weight%, the effect of increasing adhesion with the asphalt primer due to its use may be insufficient, and if it exceeds 2.5 weight%, the applicability of the emulsified asphalt may decrease.
[0057] Next, the acrylic binder resin among the components of the asphalt composition plays a role in improving the bonding strength of recycled aggregates together with straight asphalt. If its content in the asphalt composition is less than 2.0 weight%, the effect of improving the mechanical properties of the emulsified asphalt layer due to its use may be insufficient, and if it is used in excess of 8.5 weight%, the impact resistance may decrease after the emulsified asphalt layer hardens, which may cause cracks.
[0058] In addition, the acrylic binder resin uses an acrylic copolymer resin obtained by copolymerizing a mixture comprising a hydroxylpropyl acrylate monomer, an aromatic vinyl monomer represented by the following chemical formula 3, a chain transfer agent, a polymerization initiator, and a solvent, preferably comprising 55 to 60 weight% of hydroxylpropyl acrylate monomer, 5 to 10 weight% of the aromatic vinyl monomer, 4 to 8 weight% of the chain transfer agent, 0.01 to 0.5 weight% of the polymerization initiator, and the remaining amount of solvent out of a total of 100 weight%, more preferably comprising 55 to 58 weight% of hydroxylpropyl acrylate monomer, 5 to 8 weight% of the aromatic vinyl monomer, 5 to 8 weight% of the chain transfer agent, 0.01 to 0.5 weight% of the polymerization initiator, and the remaining amount of solvent out of a total of 100 weight%.
[0059] [Chemical Formula 3]
[0060]
[0061] R of Chemical Formula 3 1 is a hydrogen atom or a C1-C3 alkyl group, preferably a hydrogen atom. And, R of Chemical Formula 3 2 is a C1-C3 alkylene group, preferably a propylene group. In addition, R of Formula 3 3 and R 4 Each is independently a hydrogen atom or a straight-chain C1-C5 alkyl group, preferably a hydrogen atom or a methyl group.
[0062] The chain transfer agent used in the manufacture of acrylic binder resin may include one or more selected from CPDA (4-cyano-4-(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid), DDMAT (S-Dodecyl-S'-(α,α'-dimethyl-α"-aceticacid)trithiocarbonate) and CPDB (2-cyano-2-propyl benzodithioate).
[0063] The polymerization initiator used in the manufacture of acrylic binder resins is C1~C 10 It may include one or more selected from alkyllithium, sodium alkoxide, potassium alkoxide, and lithium sulfonate, and preferably may include C2 to C5 alkyllithium or lithium sulfonate.
[0064] The solvent used in the manufacture of the acrylic copolymer resin may include one or more selected from n-pentane, n-hexane, n-heptane, isooctane, cyclohexane, toluene, benzene, and xylene, and preferably may include one or more selected from n-hexane, n-heptane, and cyclohexane.
[0065] Next, among the components of the asphalt composition, the flux oil is a liquid oil obtained immediately before asphalt extraction during the petroleum refining process, and plays a role in improving fluidity and workability and controlling adhesive performance. The flux oil has the characteristic of melting the asphalt but adsorbing to the asphalt after paving, so as not to affect quality. If the content of the flux oil exceeds 1.0 weight% of the total weight% of the asphalt composition, it may have a negative effect on the curing and bonding strength of the emulsified asphalt, and it is appropriate to use it within the above range.
[0066] Next, among the components of the asphalt composition, the petroleum resin serves to increase the miscibility of the asphalt composition and may include one or more selected from coumarone-indene resin and C9 petroleum resin; preferably, coumarone-indene resin may be used, and more preferably, coumarone-indene resin having a softening point of 90 to 100°C may be used. Furthermore, if the petroleum resin content is less than 0.3% by weight of the total weight of the asphalt composition, the content is too low and the miscibility between the compositions may be poor, and even if used in excess of 1.0% by weight, there is no effect of increasing miscibility, so it is appropriate to use it within the above range.
[0067] Next, among the components of the asphalt composition, the surfactant plays a role in increasing the miscibility between the compositions and preventing aggregate clumping together with the petroleum resin and the dispersant, and may include one or more selected from alkyltrimethylammonium chloride, alkylpyridinium chloride, distearyldimonium chloride, dialkyldimethylammonium chloride, alkyldimethylbenzylammonium chloride, alkylisoquinolinium bromide, and alkyldimethylmetharylammonium chloride. In addition, if the surfactant content is less than 0.05 weight% of the total weight% of the asphalt composition, the content is too low, so the effect of increasing the miscibility between compositions is insufficient and the effect of preventing aggregate clumping may be insufficient, and if used in excess of 0.20 weight%, it may actually lower the mechanical properties of the paved asphalt, so it is appropriate to use it within the above range.
[0068] Next, among the components of the asphalt composition, the above-mentioned thickener serves to control the viscosity of the emulsified asphalt, and it is preferable to use hydroxypropyl methyl cellulose (HPMC) of the cellulose type. If the content exceeds 1.5 weight%, the viscosity of the emulsified asphalt may become too high and the compatibility between the recycled aggregate and the asphalt composition may decrease, so it is appropriate to use it within the above range.
[0069] Next, paraffin wax can be used as the plasticizer among the components of the asphalt composition.
[0070] Next, the vegetable emulsifier among the components of the asphalt composition plays a role in improving the storage stability of the asphalt composition, and since there is almost no additional effect of improving storage stability due to excessive use even if used in excess of 1.0 weight%, it is appropriate to use it within the above range.
[0071] Next, among the components of the asphalt composition, the dispersant plays a role in increasing the miscibility between the aggregate and the asphalt composition and increasing the fluidity of the emulsified asphalt, and is the C of polyoxyethylene glycol. 10 ~C 18 It may include fatty acid esters. Also, if the dispersant content is less than 1.0 weight% of the total weight% of the asphalt composition, aggregates in the emulsified asphalt may clump together, and using more than 3.0 weight% is an excessive use, which may actually reduce the long-term durability of the paved asphalt, so it is appropriate to use it within the above range.
[0072] Next, water acts as a solvent among the components of the asphalt composition, and the remainder of the total weight percentage of the asphalt composition, in addition to the asphalt composition described above, is used.
[0074] Among the emulsified asphalt components, the filling aggregate comprises aggregate and filling material, and may include 5 to 10 parts by weight of filling material per 100 parts by weight of aggregate.
[0075] In addition, the aggregate is an aggregate with a diameter of 1 to 20 mm, and general asphalt aggregate used in the industry can be used without limitation and may include concrete waste.
[0076] The above filler serves to fill voids that are not filled with aggregate in emulsified asphalt paving and leveled pavement layers, and may include one or more selected from limestone, cement, fly ash, recovered dust, steelmaking dust, foundry dust, blast furnace slag, and bentonite.
[0077] In the paving method of the present invention, the fourth step is a process of compacting the area where emulsified asphalt has been laid, and a general compaction method used in the industry is used.
[0078] And, the finishing step of step 5 is to clean up the area around the paved emulsified asphalt, and after the emulsified asphalt hardens, to perform painting work such as lane markings as needed.
[0080] The present invention will be explained in more detail below through examples. However, the following examples are merely illustrative to aid in understanding the present invention, and the scope of the present invention should not be interpreted as being limited to the following examples.
[0081] [Example]
[0082] Preparation Example 1: Preparation of Asphalt Primer
[0083] An asphalt primer was prepared by mixing 13.5 wt% straight asphalt (AP-5), 34.5 wt% urethane-modified silicone polymer resin, 24.5 wt% epoxy-modified acrylic copolymer resin, 6.5 wt% penetration enhancer, 2.9 wt% polyoxyethylene lauryl ether as a fluidity enhancer, and the remaining amount of solvent out of 100 wt%. At this time, the solvent used was a mixture of n-hexane, ethyl cellosolve, and furfuryl alcohol in a volume ratio of 1:0.25:0.12.
[0084] In addition, the above urethane-modified silicone polymer resin used a compound represented by the following chemical formula 1-1.
[0085] [Chemical Formula 1-1]
[0086]
[0087] In chemical formula 1-1, R 1 is -CH2O(CH3)3, and R 2 is a propylene group, and R 3 Is and R 4 is a methyl group, n is 2, and * indicates a bonding site.
[0088] And, the above epoxy-modified acrylic copolymer resin is a copolymer prepared by copolymerizing a reaction solution mixed with 52.6 wt% of a mixed monomer of 44.7 wt% glycidyl methacrylate and 55.3 wt% n-propyl methacrylate, 3.2 wt% of an acrylate represented by Chemical Formula 2-1, 0.56 wt% of 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-l-one as a polymerization initiator, and the remaining amount of methyl acetate (solvent) of 100 wt%.
[0089] The above penetration enhancer used was a mixture of potassium ethylsiliconate and 3-iodo-2-propynyl-N-butyl carbamate in a weight ratio of 1:0.35.
[0091] Experimental Example 1
[0092] The asphalt primer of Preparation Example 1 was commissioned to the Korea Institute of Construction & Living Environment Testing and Research to perform a physical property test. The test method was measured in accordance with KS M 2203:2021, and the results are shown in Table 1 below.
[0093] division unit Test results Exam location Viscosity (Engler degree, 25℃) - 4 1, 512 Gangwondaehak-gil, Chuncheon-si, Gangwon Special Self-Governing Province Sieve residue (1.18 mm) mass% 0.1 The charge of a particle - sheep Attachment - 2 / 3 or more Storage stability (24h) mass% 0.0 Evaporation residue mass% 52 Evaporation Residue - Penetration (25℃) 1 / 10 mm 101 Evaporation Residue - Scent (15℃) cm 106 Evaporation Residue - Toluene-soluble component mass% 99.27
[0095] Comparison Preparation Example 1
[0096] Asphalt primer was prepared using the same method and composition as in Preparation Example 1 above, but only 11.5 weight% of urethane-modified silicone polymer resin was used.
[0098] Comparison Preparation Example 2
[0099] Asphalt primer was prepared using the same method and composition as in Preparation Example 1 above, but without using epoxy-modified acrylic copolymer resin.
[0101] Example 1: Preparation of Emulsified Asphalt
[0102] (1) Asphalt composition
[0103] An asphalt composition was prepared by mixing 52.8 wt% of straight asphalt (AP-5), 1.4 wt% of the urethane-modified silicone polymer resin of Preparation Example 1, 5.7 wt% of an acrylic binder resin, 0.5 wt% of flux oil, 0.6 wt% of coumarone-indene resin which is a petroleum resin, 0.11 wt% of dialkyldimethylammonium chloride as a surfactant, 0.85 wt% of HPMC (Hydroxypropyl Methyl Cellulose) as a thickener, 0.36 wt% of paraffin wax as a plasticizer, 0.63 wt% of a vegetable emulsifier, 1.8 wt% of a C12 fatty acid ester of polyoxyethylene glycol as a dispersant, and the remaining amount of water which is 100 wt%.
[0104] The above acrylic binder resin used was an acrylic copolymer resin obtained by copolymerizing a mixture comprising 54.2 wt% of hydroxylpropyl acrylate monomer, 6.3 wt% of an aromatic vinyl monomer represented by chemical formula 3-1, 5.5 wt% of CPDA (4-cyano-4-(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid) as a chain transfer agent, 0.17 wt% of lithium sulfonate as a polymerization initiator, and the remaining amount of n-hexane (solvent) out of a total of 100 wt%.
[0105] [Chemical Formula 3-1]
[0106]
[0107] R1 of chemical formula 3-1 is a hydrogen atom, R2 is a C1-C3 alkylene group, preferably a propylene group, and R3 and R4 are each methyl groups.
[0108] (2) Filling aggregate
[0109] Aggregates with a diameter of 1 to 20 mm, including concrete waste, were prepared.
[0110] In addition, a filler was prepared by mixing blast furnace slag, fly ash, bentonite, and cement.
[0111] Filling aggregate was manufactured by mixing 8 parts by weight of filling material with 100 parts by weight of the above aggregate.
[0112] (3) Emulsified asphalt
[0113] Emulsified asphalt was prepared by slowly adding water while mixing and stirring the above asphalt composition and filler aggregate in a weight ratio of 1:9.2.
[0115] Comparative Example 1
[0116] Emulsified asphalt was prepared in the same manner as in Example 1 above, but without using the urethane-modified silicone polymer resin of Preparation Example 1 among the asphalt compositions, and using the same compositions in the same amounts for the remaining compositions.
[0118] Experiment 2: Adhesion Test
[0119] (1) The adhesion (adhesion strength) of asphalt primer and emulsified asphalt was measured as follows.
[0120] To compare the adhesion strength of asphalt primer and emulsified asphalt, a mortar specimen was prepared with a width of 20 cm, a length of 20 cm, and a thickness of 1 cm. Then, an asphalt primer was applied to one surface of the mortar specimen to a thickness of 0.1 mm, and then emulsified asphalt was applied to a thickness of 2 cm and cured to produce a test specimen.
[0121] Next, the test specimens were completely submerged in water and removed after 1, 3, and 7 days, and the degree of detachment of the emulsified asphalt layer was measured by sensory evaluation, and the results are shown in Table 2 below. The evaluation was evaluated as passing if no detachment of the emulsified asphalt layer was observed, and as failing if detachment occurred.
[0122] Asphalt primer emulsified asphalt 1 day 3 days 7 days Preparation Example 1 Example 1 Passed Passed Passed Comparison Preparation Example 1 Example 1 Passed Passed Failure Comparison Preparation Example 2 Example 1 Passed Failure Failure Preparation Example 1 Comparative Example 1 Passed Passed Failure
[0123] Looking at the physical property measurement results in Table 2 above, Comparative Preparation Example 1, which used less than 25% by weight of urethane-modified silicone polymer resin among the asphalt primer components, showed a result of relatively lower long-term adhesion compared to using the asphalt primer of Preparation Example 1.
[0124] In addition, when Comparative Preparation Example 2, which did not use epoxy-modified acrylic copolymer resin among the asphalt primer components, and Comparative Example 1, which did not use urethane-modified silicone polymer resin in the emulsified asphalt, were used, the long-term adhesion was insufficient compared to the case where construction was performed with the primer of Preparation Example 1 and the emulsified asphalt of Example 1.
[0125] (2) The tensile adhesion strength of asphalt primer and emulsified asphalt was evaluated by tensile testing of specimens according to ASTM D 4541, Pull-off Strength test method, and the results are shown in Table 3 below.
[0126] In addition, as asphalt primers, commercially available SSC-1 was used for Control 1, and commercially available RSC-4 was used for Control 2.
[0127] Asphalt primer emulsified asphalt Tensile bond strength (Mpa) Control group 1 (SSC-1) Example 1 0.86 Control group 2 (RSC-4) Example 1 0.87 Preparation Example 1 Example 1 0.98 Comparison Preparation Example 1 Example 1 0.92 Comparison Preparation Example 2 Example 1 0.94 Preparation Example 1 Comparative Example 1 0.90
[0128] Looking at the tensile bond strength measurement results in Table 3 above, when the primer of Preparation Example 1 was used as the asphalt primer or the emulsified asphalt of Example 1 was used as the emulsified asphalt, the tensile bond strength was relatively higher compared to Control Group 1 and Control Group 2.
[0129] In particular, it was confirmed that specimens prepared with the asphalt primer and emulsified asphalt of the present invention possessed the highest tensile bond strength (adhesion).
[0131] Examples 2 to 3 and Comparative Examples 2 to 4
[0132] Emulsified asphalt was prepared in the same manner as in Example 1 above, but an asphalt composition having the composition shown in Table 4 below was prepared, and then mixed with filler aggregate to prepare each emulsified asphalt.
[0133] division Example 1 Example 2 Example 3 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Weight ratio of asphalt composition and fill aggregate 1 :9.2 1 :9.2 1 :9.2 1 :9.2 1 :9.2 1 :9.2 1 :9.2 Asphalt composition (weight%) Straight asphalt 52.8 52.8 52.8 52.8 52.8 52.8 52.8 Urethane-modified silicone polymer resin 1.4 1.4 1.4 1.4 1.4 1.4 1.4 Acrylic binder resin 5.7 4.0 8.0 1.0 10.2 5.7 5.7 Flux oil 0.5 0.5 0.5 0.5 0.5 0.5 0.5 petroleum balance 0.6 0.6 0.6 0.6 0.6 0.6 0.6 surfactants 0.11 0.11 0.11 0.11 0.11 0.11 0.48 Thickener 0.85 0.85 0.85 0.85 0.85 0.85 0.85 plasticizer 0.36 0.36 0.36 0.36 0.36 0.36 0.36 Vegetable emulsifier 0.63 0.63 0.63 0.63 0.63 0.63 0.63 Dispersant 1.8 1.8 1.8 1.8 1.8 0 1.8 water The remaining amount of 100 weight%
[0135] Experiment 2: Measurement of Physical Properties of Emulsified Asphalt
[0136] The tensile strength, toughness, non-stickiness, and presence or absence of plastic shrinkage cracks of the emulsified asphalt prepared in Examples 1 to 3 and Comparative Examples 2 to 4 were measured, and the results are shown in Table 5 below.
[0137] Tensile strength (tenacity, N / mm²) 2 Toughness is the most important mechanical property that enables asphalt pavement to withstand loads caused by wheel loads, and it is a physical property related to the expected lifespan of the road pavement. Toughness (N·mm) is the strength of the solid state of emulsified asphalt, and a higher value indicates higher durability. Non-tackiness refers to the degree of low adhesion to construction vehicle tire materials.
[0138] Non-stickiness was measured by applying emulsified asphalt over an asbestos packing and curing it, laying a rubber plate made of the same material as a truck tire on the cured emulsified asphalt, running a roller under a constant load, removing the rubber plate, and measuring the weight of the emulsified asphalt adhering to the rubber plate. The adhesion rate (%) was calculated based on Equation 1, and the lower the adhesion rate, the better the non-stickiness.
[0139] Plastic shrinkage cracks were measured by whether cracks occurred within 3 days of the cured emulsified asphalt used for the above non-stick measurement.
[0140] [Equation 1]
[0141] Adhesion rate (%) = (Weight of emulsified asphalt on rubber sheet / Weight of emulsified asphalt sprayed on asbestos packing) × 100%
[0142] division Tensile strength (N / mm²) 2 ) Toughness (N·mm) Adhesion rate (%, non-stick) Whether water shrinkage cracks occur Example 1 1.47 102 4.3 × Example 2 1.38 95 8.9 × Example 3 1.50 107 3.8 × Comparative Example 2 1.14 82 12.3 × Comparative Example 3 1.56 111 3.5 ○ Comparative Example 4 1.08 83 8.4 ○ Comparative Example 5 1.28 93 7.6 ×
[0143] Looking at the physical property measurement results in Table 5 above, the emulsified asphalt of Examples 1 to 3 is 1.30 N / mm 2 It showed high durability with a tensile strength of over 90 N·mm and toughness of over 90 N·mm, excellent non-stick properties with an adhesion rate of less than 10%, and results in no water shrinkage cracking.
[0144] In contrast, Comparative Example 2, in which an acrylic binder resin was used in an amount of less than 2.0 wt% as an emulsified asphalt composition, showed significantly insufficient tensile strength and toughness compared to Example 1 and Example 2, and a tendency for the adhesion rate to increase significantly.
[0145] In addition, Comparative Example 3, which used more than 8.5 weight% of acrylic binder resin, had a low adhesion rate and had somewhat higher tensile strength and toughness compared to Example 3, but had a problem with water shrinkage cracking.
[0146] In addition, Comparative Example 4, which did not use a dispersant as an emulsified asphalt composition, showed overall poor physical properties.
[0147] In addition, in the case of Comparative Example 5, in which a surfactant content exceeding 0.20 wt% was used, the tensile strength and toughness were actually reduced compared to Examples 1 to 3.
[0149] Manufacturing Example: Road paving construction
[0150] Asphalt road paving was performed using the asphalt primer prepared in Preparation Example 1 and the emulsified asphalt prepared in Example 1, and the actual construction photograph is shown in Fig. 1.
[0152] The above description is merely an example of an embodiment of the present invention, and those skilled in the art may implement it in modified forms without departing from the essential characteristics of the present invention. Accordingly, the scope of the present invention should not be limited to the aforementioned embodiment but should be interpreted to include various embodiments within the scope equivalent to that described in the claims.
Claims
Claim 1 A paving method with improved adhesion and durability using emulsified asphalt, comprising a process including: Step 1, performing surface preparation on an asphalt road; Step 2, applying an asphalt primer to the surface prepared in Step 1 to form a primer layer; Step 3, laying emulsified asphalt on the primer layer; Step 4, compacting the laid area; and Step 5, performing a finishing treatment; wherein the asphalt primer comprises straight asphalt, urethane-modified silicone polymer resin, epoxy-modified acrylic copolymer resin, penetration enhancer, fluidity enhancer, and a solvent. Claim 2 A paving method with improved adhesion and durability utilizing emulsified asphalt, characterized in that, in claim 1, the emulsified asphalt comprises an asphalt composition including straight asphalt, urethane-modified silicone polymer resin, acrylic binder resin, flux oil, petroleum resin, surfactant, thickener, plasticizer, vegetable emulsifier, dispersant, and water; recycled aggregate including aggregate and filler; and water. Claim 3 A paving method with improved adhesion and durability using emulsified asphalt according to claim 1 or 2, characterized in that the urethane-modified silicone polymer resin comprises a compound represented by the following chemical formula 1; [Chemical Formula 1] In Chemical Formula 1, R 1 is -CH2OCH2CH3, -CH2OCH(CH3)2 or -CH2O(CH3)3, and R 2 is a C2–C3 straight-chain alkylene group, and R 3 Is is, R 4 is a hydrogen atom, a C1-C3 straight-chain alkyl group, or -CH2OCH3, and m is an integer from 1 to 3. Claim 4 A paving method with improved adhesion and durability using emulsified asphalt according to claim 1, wherein the epoxy-modified acrylic copolymer resin comprises a copolymer obtained by copolymerizing a reaction solution comprising a mixed monomer comprising glycidyl methacrylate and n-propyl methacrylate, an acrylate represented by the following chemical formula 2, a polymerization initiator, and a solvent, wherein the mixed monomer comprises 40 to 50 weight% of glycidyl methacrylate and the remainder of n-propyl methacrylate in the total weight; [Chemical Formula 2] In Chemical Formula 2, R 1 is a C2–C5 straight-chain alkylene group, and R 2 It is a hydrogen atom or -OR 3 is, R 3 is a C1-C8 straight-chain alkyl group or a phenyl group. Claim 5 A paving method with improved adhesion and durability using emulsified asphalt, characterized in that, in claim 4, the reaction solution comprises 50 to 55 weight% of the mixed monomer, 2.0 to 3.5 weight% of the acrylate represented by Chemical Formula 2, 0.2 to 1.5 weight% of the polymerization initiator, and the remaining amount of the solvent among 100 weight%. Claim 6 A paving method with improved adhesion and durability using emulsified asphalt according to claim 2, wherein the acrylic binder resin is an acrylic copolymer resin obtained by copolymerizing a mixture comprising a hydroxylpropyl acrylate monomer, an aromatic vinyl monomer represented by the following chemical formula 3, a chain transfer agent, a polymerization initiator, and a solvent; [Chemical Formula 3] R of Chemical Formula 3 1 is a hydrogen atom or a C1–C3 alkyl group, and R 2 is a C1–C3 alkylene group, and R 3 and R 4 Each is independently a hydrogen atom or a straight-chain C1-C5 alkyl group. Claim 7 A paving method with improved adhesion and durability using emulsified asphalt according to claim 1, wherein the penetration enhancer comprises potassium (C1-C5 alkyl) siliconate and 3-iodo-2-propynyl-N-butyl carbamate, the fluidity enhancer comprises 12 to 16 weight% of polyoxyethylene lauryl ether and 84 to 88 weight% of hydrocarbon oil having an aromatic compound content of less than 0.5 weight%, and the solvent comprises one or more selected from n-hexane, ethyl cellosolve, and furfuryl alcohol. Claim 8 A paving method with improved adhesion and durability using emulsified asphalt, characterized in that, in claim 1, the asphalt primer satisfies a viscosity (Angler degree, 25℃) of 4 according to KS M 2203:2021 standards. Claim 9 A paving method with improved adhesion and durability using emulsified asphalt, characterized by further performing one of the following processes: a process of forming a surface coating layer by coating with a peelcoat agent between steps 4 and 5 in claim 1; and a process of forming a surface coating layer with an asphalt tack coating spray. Claim 10 An asphalt road paved by any one of the paving methods selected from paragraphs 1 through 9.
